Demineralization of Osseous Structures as Presentation of a Rare Genetic Disorder That Is Associated With a High Rate of Mortality - Adeeba Afrah; Michael A. Finkel; Carolina Fonseca; Marianne Tomiyoshi Asato; M. Susan Jay; Athina Pappas; Shashikala B. Gowda; Allison Jay (Case Reports in Endocrinology)
Conclusions: This case accentuates the importance of considering rare genetic disorders in neonates with complex clinical presentations and affirms the need for comprehensive counseling and education, particularly in consanguineous parents, to address familial implications and guide appropriate interventions.